Ordered proton exchange membrane and preparation method thereof
By setting grooves on the surface of the proton exchange membrane anode and adding a reinforcement layer, the problems of high manufacturing cost and unstable consistency of membrane electrodes are solved, and the performance and durability of the PEM electrolytic cell are improved.
Patent Information
- Application Number
- CN202411679328.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-03
AI Technical Summary
The existing membrane electrodes have high manufacturing costs, easy catalytic layer to fall off, and unstable process consistency, which affects the performance and durability of the PEM electrolytic cell.
Several grooves are provided on the anode surface of the proton exchange membrane, and the grooves are imprinted by coating resin slurry on the base film and imprinting the grooves after drying to form an ordered proton exchange membrane, and adding a puffed polytetrafluoroethylene reinforcement layer to improve the membrane stability.
The service life and performance of the PEM electrolytic cell are improved, and the surface channels between the catalytic layer and the proton exchange membrane are constructed through surface modification, which enhances the stability and performance of the membrane electrode.
Smart Images

Figure CN119243250A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field, and particularly relates to an ordered proton exchange membrane and a preparation method thereof. Background Art
[0002] As one of the core components of PEM electrolyzer (PEMWE), membrane electrode directly affects the performance and durability of the battery. At present, membrane electrode is mainly composed of catalyst layer and proton exchange membrane (PFSA). In the existing technology, membrane electrode still has technical problems such as high manufacturing cost, easy detachment of catalyst layer, stratification, etc., and there are problems such as unstable process consistency and long preparation time in the preparation process.
[0003] At present, the main performance of PEM electrolyzer is still achieved by membrane electrode, and membrane electrode (MEA) is mainly composed of proton exchange membrane, catalyst layer (CL) and gas diffusion layer (GDL). Its performance mainly depends on the content of precious metals in the loaded catalyst and the supporting role of the proton exchange membrane. The preparation conditions of the catalyst layer are complex and the cost is high. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.
[0005] As one aspect of the present invention, the present invention provides an ordered proton exchange membrane, which comprises: a plurality of grooves are arranged on the surface of the anode side of the proton exchange membrane.
[0006] As a preferred solution of the ordered proton exchange membrane described in the present invention: the grooves are strip-shaped, and the strip-shaped grooves are arranged in a horizontal array.
[0007] As a preferred solution for the ordered proton exchange membrane described in the present invention: taking 1 / 2 of the vertical distance from the vertex (0) to the bottom point (P) of the groove as the boundary, the part protruding from the boundary is the protruding area, and the part recessed from the boundary is the compressed area, and the area ratio of the protruding area to the compressed area is 1:0.2~5.
[0008] As a preferred solution of the ordered proton exchange membrane of the present invention: the depth (T) of the groove is 1-10% of the thickness of the ordered proton exchange membrane.
[0009] As a preferred solution of the ordered proton exchange membrane described in the present invention: the grooves include curved strips or straight strips.
[0010] As a preferred embodiment of the ordered proton exchange membrane of the present invention: the proton exchange membrane comprises a perfluorosulfonic acid proton exchange membrane.
[0011] The present invention also provides the method for forming an ordered proton exchange membrane, which comprises coating a resin slurry on a base membrane, drying the slurry, and stamping a plurality of grooves on the surface of the dried slurry to obtain the ordered proton exchange membrane.
[0012] As a preferred embodiment of the method of the present invention, the method further comprises the step of pre-curing the resin slurry at 55-80° C. before coating the resin slurry on the base film.
[0013] As a preferred solution of the method of the present invention, it also includes preparing a reinforced proton exchange membrane, adding several layers of expanded polytetrafluoroethylene reinforcement layers in the middle of the proton exchange membrane, and coating the resin slurry between every two layers of expanded polytetrafluoroethylene reinforcement layers.
[0014] As a preferred embodiment of the method of the present invention, it comprises the following steps:
[0015] (1) adding a perfluorinated resin into a solvent and mixing to obtain a perfluorinated resin dispersion;
[0016] (2) heat-aging the perfluorinated resin dispersion at 55 to 80° C. to obtain a slurry;
[0017] (3) coating: coating the slurry on the base film, laminating the expanded polytetrafluoroethylene reinforcement layer on the slurry, and then coating the slurry and laminating the expanded polytetrafluoroethylene reinforcement layer in sequence, wherein the expanded polytetrafluoroethylene reinforcement layer is set to 1 to 4 layers, and finally coating a layer of slurry, and heating and drying;
[0018] (4) Coating: Imprinting: Imprinting the grooves on the surface of the proton exchange membrane obtained in step (3), followed by heating at 120-160° C. to obtain the ordered proton exchange membrane.
[0019] Preferably, the solvent in step (1) comprises an alcohol solvent, N,N-dimethylformamide (DMF); preferably, the alcohol solvent comprises isopropanol and / or n-propanol, N,N-dimethylformamide (DMF).
[0020] Preferably, the viscosity of the slurry coated on the outermost layer on one side of the anode is lower than the viscosity of the slurry of other layers.
[0021] Preferably, the viscosity of the slurry coated on the outermost layer of the anode side is 70-140 cps.
[0022] Preferably, in step (3), the temperature of heating and drying is 60 to 90°C.
[0023] Beneficial effects of the present invention: The present invention utilizes surface modification means in the preparation process of proton exchange membrane to prepare ordered PFSA, construct the surface channels of the catalytic layer and the proton exchange membrane, thereby improving the service life and performance of the PEM electrolyzer (PEMWE). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0025] Figure 1 This is a three-dimensional image of the perfluorosulfonic acid proton exchange membrane obtained in step (3) of Example 1 without being printed.
[0026] Figure 1 In the figure, 1 is a layer of slurry 2 coated for the fourth time, 2 is the third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, 3 is a layer of slurry 1 coated for the third time, 4 is the second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, 5 is a layer of slurry 1 coated for the second time, 6 is the first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, 7 is a layer of slurry 1 coated for the first time, and 8 is a base film.
[0027] Figure 2 This is a three-dimensional image of the ordered proton exchange membrane obtained in Example 1.
[0028] Figure 2 In the figure, 9 is a layer of slurry 2 coated for the fourth time and embossed, 10 is a third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, 11 is a layer of slurry 1 coated for the third time, 12 is a second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, 13 is a layer of slurry 1 coated for the second time, 14 is a first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, 15 is a layer of slurry 1 coated for the first time, and 16 is a base film.
[0029] Figure 3 This is a side cross-sectional view of the strip-shaped groove in Example 1.
[0030] Figure 4 This is a scanning electron microscope image of the ordered proton exchange membrane (PFSA) product obtained in the present invention.
[0031] Figure 5 For electrochemical life test.
[0032] Figure 6 For IV performance testing.
[0033] Figure 7 A side cross-sectional view of a preferred size of the strip array grooves of Example 1. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0035] Embodiment 1:
[0036] The ordered proton exchange membrane (PFSA) of the present invention has a structure in which a plurality of grooves are arranged on the surface of one side of the anode of the proton exchange membrane.
[0037] Preferably, the grooves are in the shape of straight strips, and the strip-shaped grooves are arranged in a horizontal array. The horizontal array arrangement means that the straight strip-shaped grooves are arranged parallel to each other, and the spacing between the grooves is equal.
[0038] The boundary is 1 / 2 of the vertical distance from the vertex 0 of the groove to the bottom point P. The part protruding from the boundary is the protruding area, and the part recessed from the boundary is the compressed area. The area ratio of the protruding area to the compressed area is 1:0.2~5.
[0039] The depth T of the groove (ie, the vertical distance from the vertex 0 to the bottom point P) is 1-10% of the thickness of the ordered proton exchange membrane.
[0040] Preferably, the proton exchange membrane comprises a perfluorosulfonic acid proton exchange membrane.
[0041] As an alternative, the plurality of grooves disposed on the surface of one side of the proton exchange membrane anode may also be curved strip-shaped grooves, such as wavy strip-shaped grooves.
[0042] The method for preparing an ordered proton exchange membrane (PFSA) of the present invention comprises the step of printing a plurality of grooves on the slurry surface at one side of the anode of the proton exchange membrane.
[0043] Preferably, the proton exchange membrane comprises a perfluorosulfonic acid proton exchange membrane, specifically, the method comprises coating a perfluorinated resin slurry on a base membrane, drying the slurry, and stamping a plurality of grooves to obtain an ordered proton exchange membrane (PFSA).
[0044] Preferably, before coating the perfluorinated resin slurry on the base film, the perfluorinated resin slurry is kept at 60-80° C. for 1 hour to mature the perfluorinated resin slurry.
[0045] As one of the preferred embodiments, it also includes preparing a reinforced perfluorosulfonic acid proton exchange membrane. Specifically, several layers of expanded polytetrafluoroethylene (ePTFE) reinforcement layers are added in the middle of the proton exchange membrane, and perfluorinated resin slurry is coated between every two layers of expanded polytetrafluoroethylene (ePTFE) reinforcement layers.
[0046] One of the preferred preparation methods of the ordered perfluorosulfonic acid proton exchange membrane (PFSA) of the present invention comprises the following steps:
[0047] (1) Preparation of resin dispersion slurry: Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 50 parts of isopropanol, 20 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 min to obtain a dispersion 1 with a viscosity of 150 cps.
[0048] Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 30 parts of isopropanol and 50 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 minutes to obtain a dispersion 2 with a viscosity of 100 cps.
[0049] (2) Aging treatment: The obtained dispersion 1 and dispersion 2 were placed in an oven at 60° C. for 25 min to obtain slurry 1 and slurry 2, respectively.
[0050] (3) First coating: a layer of slurry 1 is coated on one side of the polyimide (PI) base film, with a coating thickness of about 200 μm, and a first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer (thickness of about 12±3 μm, DONALDSON, 380124E1) is attached to the surface of the coated slurry 1, and the temperature is kept at 60°C for 20 min;
[0051] Second coating: after cooling, a layer of slurry 1 is coated on the surface of the first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 70° C. for 20 minutes;
[0052] The third coating: after cooling, a layer of slurry 1 is coated on the surface of the second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 80°C for 20 minutes;
[0053] Fourth coating: After cooling, a layer of slurry 2 was coated on the surface of the third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 250 μm, and the temperature was kept at 90°C for 25 minutes to obtain a perfluorosulfonic acid proton exchange membrane ( Figure 1 ).
[0054] (4) Imprinting: Imprinting is performed on the surface of the perfluorosulfonic acid proton exchange membrane obtained in step (3) and coated with the slurry 2 using a nanoimprinting process. Specifically, strip array grooves are imprinted on the surface of the perfluorosulfonic acid proton exchange membrane, so that ordered channels are formed on the surface of the perfluorosulfonic acid proton exchange membrane.
[0055] (5) After printing, the obtained perfluorosulfonic acid proton exchange membrane is kept at 140°C for 40 minutes to obtain an ordered proton exchange membrane. The side with the ordered channels is the anode, and the anode catalyst layer can be coated or transferred on the anode. Figure 2 As shown, Figure 2 This is a stereoscopic diagram of the ordered proton exchange membrane obtained in the present invention. Figure 3 It is a side cross-sectional view of a strip groove. Figure 7 A preferred size of the strip array grooves printed on the surface of the perfluorosulfonic acid proton exchange membrane is given, such as Figure 7 As shown, the groove depth of the strip array is 3 μm, the width of the protruding area is 1 μm, and the width of the compressed area is 3 μm.
[0056] Assemble the membrane electrode for IV performance test and electrochemical life test: The catalyst-coated membrane (CCM) is assembled between a 0.4 mm thick titanium felt at the anode and a 0.24 mm thick gas diffusion layer (GDL) at the cathode and two polytetrafluoroethylene gaskets to form a membrane electrode assembly (MEA). The effective electrode area is 25 cm 2 The platinum loading of the anode CL is 1.0 mg lr / cm 2 The platinum loading of the cathode CL is 0.4 mgPt / cm 2 The anode gasket is 140um thick, the cathode gasket is 100um thick, the hardware is tightened with a torque of 8N-m, and the flow rate of circulating water at 60℃ and 100mL / min is 0A / cm 2 -0.5A / cm 2 -1A / cm 2 -2A / cm 2 After 15 min activation, at 2A / cm 2 The chemical life test is carried out at a current density of more than 1000 hours to determine the voltage change trend and calculate the performance decay rate of CCM ( Figure 5 ).
[0057] The IV performance test was performed at 60°C with a circulating water flow rate of 100 mL / min and a test step size of 0.5 A / cm 2 Test and record 0A / cm 2 -1A / cm 2 -2A / cm 2 -3A / cm 2 Corresponding voltage data ( Figure 6 ). All tests were carried out on a PEM water electrolysis test bench.
[0058] Embodiment 2:
[0059] One of the preparation methods of perfluorosulfonic acid proton exchange membrane (PFSA) is as follows:
[0060] (1) Preparation of resin dispersion slurry: Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 50 parts of isopropanol, 20 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 min to obtain a dispersion 1 with a viscosity of 150 cps.
[0061] Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 30 parts of isopropanol and 50 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 minutes to obtain a dispersion 2 with a viscosity of 100 cps.
[0062] (2) First coating: The obtained dispersion 1 and dispersion 2 are used as slurry 1 and slurry 2 respectively, and a layer of slurry 1 is coated on one surface of the polyimide (PI) base film, and the coating thickness is about 200 μm. The first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer (thickness of about 12±3 μm, DONALDSON, 380124E1) is attached to the surface of the coated slurry 1, and the temperature is kept at 60°C for 20 min;
[0063] Second coating: after cooling, a layer of slurry 1 is coated on the surface of the first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 70° C. for 20 minutes;
[0064] The third coating: after cooling, a layer of slurry 1 is coated on the surface of the second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 80°C for 20 minutes;
[0065] Fourth coating: after cooling, a layer of slurry 2 was coated on the surface of the third commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer with a coating thickness of about 250 μm. The mixture was kept at 90° C. for 25 min to obtain a perfluorosulfonic acid proton exchange membrane.
[0066] (3) Imprinting: Imprinting is performed on the surface of the perfluorosulfonic acid proton exchange membrane obtained in step (2) coated with the slurry 2 using a nanoimprinting process. Specifically, strip array grooves (the same as in Example 1) are imprinted on the surface of the perfluorosulfonic acid proton exchange membrane, so that ordered channels are formed on the surface of the perfluorosulfonic acid proton exchange membrane.
[0067] (4) After the printing, the obtained perfluorosulfonic acid proton exchange membrane is kept at 140° C. for 40 minutes to obtain an ordered perfluorosulfonic acid proton exchange membrane. The side with the ordered channels is the anode, and the anode catalyst layer can be coated or transferred on the anode later.
[0068] Embodiment 3:
[0069] One of the preparation methods of the perfluorosulfonic acid proton exchange membrane (PFSA) of the present invention comprises the following steps:
[0070] (1) Preparation of resin dispersion slurry: Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 50 parts of isopropanol, 20 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 min to obtain a dispersion 1 with a viscosity of 150 cps.
[0071] Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 30 parts of isopropanol and 50 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 minutes to obtain a dispersion 2 with a viscosity of 100 cps.
[0072] (2) Aging treatment: The obtained dispersion 1 and dispersion 2 were placed in an oven at 60° C. for 25 min to obtain slurry 1 and slurry 2, respectively.
[0073] (3) First coating: a layer of slurry 1 is coated on one side of the polyimide (PI) base film, with a coating thickness of about 200 μm, and a first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer (thickness of about 12±3 μm, DONALDSON, 380124E1) is attached to the surface of the coated slurry 1, and the temperature is kept at 60°C for 20 min;
[0074] Second coating: after cooling, a layer of slurry 1 is coated on the surface of the first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 70° C. for 20 minutes;
[0075] The third coating: after cooling, a layer of slurry 1 is coated on the surface of the second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 80°C for 20 minutes;
[0076] Fourth coating: after cooling, a layer of slurry 2 was coated on the surface of the third commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer with a coating thickness of about 250 μm. The mixture was kept at 90° C. for 25 min to obtain a perfluorosulfonic acid proton exchange membrane.
[0077] (4) The obtained perfluorosulfonic acid proton exchange membrane is kept at 140° C. for 40 minutes to obtain a perfluorosulfonic acid proton exchange membrane. Subsequently, an anode catalyst layer can be coated or transferred on the anode.
[0078] Embodiment 4:
[0079] One of the preparation methods of the perfluorosulfonic acid proton exchange membrane (PFSA) of the present invention comprises the following steps:
[0080] (1) Preparation of resin dispersion slurry: Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 50 parts of isopropanol and 20 parts of n-propanol, and stirred at 400 rpm for 30 min to obtain dispersion 1.
[0081] Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 30 parts of isopropanol and 50 parts of n-propanol, and stirred at 400 rpm for 30 minutes to obtain dispersion 2.
[0082] (2) Aging treatment: The obtained dispersion 1 and dispersion 2 were placed in an oven at 60° C. for 25 min to obtain slurry 1 and slurry 2, respectively.
[0083] (3) First coating: a layer of slurry 1 is coated on one side of the polyimide (PI) base film, with a coating thickness of about 200 μm, and a first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer (thickness of about 12±3 μm, DONALDSON, 380124E1) is attached to the surface of the coated slurry 1, and the temperature is kept at 60°C for 20 min;
[0084] Second coating: after cooling, a layer of slurry 1 is coated on the surface of the first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 70° C. for 20 minutes;
[0085] The third coating: after cooling, a layer of slurry 1 is coated on the surface of the second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 80°C for 20 minutes;
[0086] Fourth coating: after cooling, a layer of slurry 2 was coated on the surface of the third commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer with a coating thickness of about 250 μm. The mixture was kept at 90° C. for 25 min to obtain a perfluorosulfonic acid proton exchange membrane.
[0087] (4) Imprinting: Imprinting is performed on the surface of the perfluorosulfonic acid proton exchange membrane obtained in step (3) and coated with the slurry 2 using a nanoimprinting process. Specifically, strip array grooves are imprinted on the surface of the perfluorosulfonic acid proton exchange membrane, so that ordered channels are formed on the surface of the perfluorosulfonic acid proton exchange membrane.
[0088] (5) After the printing, the obtained perfluorosulfonic acid proton exchange membrane is kept at 140° C. for 40 minutes to obtain an ordered perfluorosulfonic acid proton exchange membrane. The side with the ordered channels is the anode, and the anode catalyst layer can be coated or transferred on the anode later.
[0089] Embodiment 5:
[0090] One of the preparation methods of the perfluorosulfonic acid proton exchange membrane (PFSA) of the present invention comprises the following steps:
[0091] (1) Preparation of resin dispersion slurry: Calculated by mass fraction, 1 part of perfluorinated resin (D2020CS) (solid content 20-22%) was mixed with 50 parts of isopropanol, 20 parts of n-propanol, and 5 parts of N,N-dimethylformamide (DMF), and stirred at 400 rpm for 30 min to obtain a dispersion 1 with a viscosity of 150 cps.
[0092] (2) Aging treatment: The obtained dispersion 1 was placed in an oven at 60° C. for 25 min to obtain slurry 1.
[0093] (3) First coating: a layer of slurry 1 is coated on one side of the polyimide (PI) base film, with a coating thickness of about 200 μm, and a first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer (thickness of about 12±3 μm, DONALDSON, 380124E1) is attached to the surface of the coated slurry 1, and the temperature is kept at 60°C for 20 min;
[0094] Second coating: after cooling, a layer of slurry 1 is coated on the surface of the first layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 70° C. for 20 minutes;
[0095] The third coating: after cooling, a layer of slurry 1 is coated on the surface of the second layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer, with a coating thickness of about 200 μm, and a third layer of commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer is attached to the surface of the coated slurry 1, and the temperature is kept at 80°C for 20 minutes;
[0096] Fourth coating: After cooling, a layer of slurry 1 was coated on the surface of the third commercial expanded polytetrafluoroethylene (ePTFE) reinforcement layer with a coating thickness of about 250 μm. The mixture was kept at 90° C. for 25 min to obtain a perfluorosulfonic acid proton exchange membrane.
[0097] (4) Imprinting: Imprinting is performed on the surface of the perfluorosulfonic acid proton exchange membrane obtained in step (3) and coated with the slurry 1 using a nanoimprinting process. Specifically, strip array grooves are imprinted on the surface of the perfluorosulfonic acid proton exchange membrane, so that ordered channels are formed on the surface of the perfluorosulfonic acid proton exchange membrane.
[0098] (5) After the printing, the obtained perfluorosulfonic acid proton exchange membrane is kept at 140° C. for 40 minutes to obtain an ordered perfluorosulfonic acid proton exchange membrane. The side with the ordered channels is the anode, and the anode catalyst layer can be coated or transferred on the anode later.
[0099] Table 1
[0100]
[0101]
[0102] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An ordered proton exchange membrane, characterized in that: The method comprises: arranging a plurality of grooves on the surface of one side of the proton exchange membrane anode.
2. The ordered proton exchange membrane according to claim 1, characterized in that: The grooves are strip-shaped; the strip-shaped grooves are arranged in a horizontal array.
3. The ordered proton exchange membrane according to claim 1 or 2, characterized in that: The boundary is 1 / 2 of the vertical distance from the apex (0) to the bottom point (P) of the groove. The part protruding from the boundary is the protruding area, and the part recessed from the boundary is the compressed area. The area ratio of the protruding area to the compressed area is 1:0.2-5.
4. The ordered proton exchange membrane according to claim 1 or 2, characterized in that: The depth (T) of the groove is 1-10% of the thickness of the ordered proton exchange membrane.
5. The ordered proton exchange membrane according to claim 1, characterized in that: The grooves may be in a straight strip shape or a curved strip shape.
6. The ordered proton exchange membrane according to any one of claims 1, 2 or 5, characterized in that: The proton exchange membrane comprises a perfluorosulfonic acid proton exchange membrane.
7. The method for preparing the ordered proton exchange membrane according to claim 1, characterized in that: The method comprises the steps of coating a resin slurry on a base film, drying the slurry, and pressing a plurality of grooves on the surface of the dried slurry to obtain an ordered proton exchange membrane.
8. The method according to claim 7, characterized in that: The method also includes preserving the resin slurry at 55 to 80° C. for aging treatment before coating the resin slurry on the base film.
9. The method according to claim 8, characterized in that: The method also includes preparing a reinforced proton exchange membrane, adding several layers of expanded polytetrafluoroethylene reinforcement layers in the middle of the proton exchange membrane, and coating the middle of every two layers of expanded polytetrafluoroethylene reinforcement layers with resin slurry.
10. The method according to claim 9, characterized in that: The following steps are included: (1) adding a perfluorinated resin into a solvent and mixing to obtain a perfluorinated resin dispersion; (2) heat-aging the perfluorinated resin dispersion at 55 to 80° C. to obtain a slurry; (3) coating: coating the slurry on the base film, laminating the expanded polytetrafluoroethylene reinforcement layer on the slurry, and then coating the slurry and laminating the expanded polytetrafluoroethylene reinforcement layer in sequence, wherein the expanded polytetrafluoroethylene reinforcement layer is set to 1 to 4 layers, and finally coating a layer of slurry, and heating and drying; (4) Coating: Imprinting: Imprinting the grooves on the surface of the proton exchange membrane obtained in step (3), followed by heating at 120-160° C. to obtain the ordered proton exchange membrane.
